Moisture sorption isotherms of sesame flour at several temperatures - Menkov, Nikolay D. (Array, 2007)
Moisture equilibrium data (adsorption and desorption) of sesame flour were determined using the static gravimetric method of saturated salt solutions at three temperatures, 10, 25 and 40 °C. The range of water activities for each temperature was between 0.11 and 0.85. Equilibrium moisture content decreased with the increase in storage temperature at any given water activity. The experimental data were fitted by five mathematical models (modified Oswin, modified Halsey, modified Chung-Pfost, modified Henderson and Guggenheim-Anderson-de Boer (GAB)). The GAB model was found to be the most suitable for describing the sorption data. The monolayer moisture content was estimated using the Brunauer-Emmett-Teller equation